1984
DOI: 10.1161/01.atv.4.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation in the renal arteries.

Abstract: S tenosis of the renal artery is most commonly produced by atherosclerosis.1 Within the renal artery the proximal 1 or 2 cm of the main renal artery is typically the site of maximal atherosclerotic involvement.1 In an autopsy study of 500 cases, ranging in age from 0 to 80 years, evidence of atherosclerosis in the renal arteries was first found in the second decade of life in the form of fatty streaks. 2 In the second decade of life, 43% of cases showed renal atherosclerosis, and by the sixth decade, 82% of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previously reported in vivo flow measurements in aorta and renal arteries (Sabbah et al 1984) were used to determine the appropriate boundary conditions for the CFD analysis. To ensure that the flow entering the renal arteries was fully developed, a parabolic streamwise velocity profile (Equation (1)) was implemented as an inlet boundary condition.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported in vivo flow measurements in aorta and renal arteries (Sabbah et al 1984) were used to determine the appropriate boundary conditions for the CFD analysis. To ensure that the flow entering the renal arteries was fully developed, a parabolic streamwise velocity profile (Equation (1)) was implemented as an inlet boundary condition.…”
Section: Resultsmentioning
confidence: 99%
“…24 This phenomenon might be the result of a physiologic flow reversal, as it is seen in some pulsatile flow studies. 31 Figure 3 shows the time dependent study for the physiological and the most severe pathological condition. The pressure variation shows the dependence of the position in the arterial tree and follows a gradual proximal to distal distribution.…”
Section: Resultsmentioning
confidence: 99%
“…At angles close to perpendicular or obtuse angles, the curvature of the streamlines increases, causing backflow and vorticity, which lowers pressure [16] . This turbulent flow increases the turbulent kinetic energy (TKE), which can impair endothelial function, resulting in a higher risk of atherosclerosis development in the region of renal artery branching [17] . It has been demonstrated that disturbed flow might be associated with serious negative effects such as atherosclerosis [18] or aneurysm [19] .…”
Section: Introductionmentioning
confidence: 99%